Coexistence of three blaKPC-2 genes on an IncF/IncR plasmid in ST11 Klebsiella pneumoniae. (June 2019) - Feng, Yu; Liu, Lu; McNally, Alan; Zong, Zhiyong
Highlights: Three bla KPC-2 genes co-existed on an IncFII/R plasmid of a ST11 Klebsiella pneumoniae . Three copies of the IS 26 –IS Kpn27 – bla KPC-2 –IS Kpn6 –IS 26 unit were present in tandem. Multiple IS 26 copies are key factor in genetic plasticity and could mediate gene multiplication. Abstract: Objectives: Here we report the finding of three copies of the bla KPC-2 gene on a plasmid in ST11 Klebsiella pneumoniae . Methods: Carbapenem-resistant K. pneumoniae clinical strain WCHKP2 was subjected to whole-genome sequencing (WGS) using both a short-read Illumina HiSeq X10 platform and long-read MinION sequencer. Hybrid assembly was performed using Unicycler, and contigs were corrected using Pilon. Based on WGS, the sequence type (ST), capsular type, plasmid replicon type and plasmid multilocus sequence type were determined and virulence and antimicrobial resistance genes were identified. Mating was performed to identify a self-transmissible plasmid mediating carbapenem resistance. Results: Strain WCHKP2 was resistant to imipenem [minimum inhibitory concentration (MIC) = 64 μg/mL] and meropenem (MIC = 128 μg/mL). Strain WCHKP2 had a 5 477 148-bp circular chromosome, two small ColRNAI-like plasmids (5596 bp and 10 060 bp), and one large plasmid (177 516 bp, designated pKPC2_020002) containing an IncR and an IncFII replicon. Surprisingly, there were three copies of the bla KPC-2 carbapenemase gene on pKPC2_020002, which was not self-transmissible. Each of the bla KPC-2 genes was located in the same genetic context with insertion sequence IS Kpn27 upstream and IS Kpn6 downstream and bracketed by IS 26 . The three copies of the IS 26 –IS Kpn27 – bla KPC-2 –IS Kpn6 –IS 26 unit were present in tandem. Conclusion: Here we report the surprising co-existence of three copies of bla KPC-2 on an IncR/IncF plasmid due to the action of IS 26 . Multiple copies of IS 26 are a key factor generating genetic plasticity and could mediate the multiplication of resistance genes.